Abordagem heurística para reagrupamento de conjuntos de consumidores de uma distribuidora de energia elétrica - Pereira, Wanderson Lombardy (2022)
The evaluation of the performance of distributors is governed by the National Electric Energy Agency – ANEEL through the Collective and Individual Performance Indicators, presented in Module 8 of the Distribution Procedures (PRODIST). These indicators aim at setting targets for a minimum level of acceptable quality in the service provided by the distribution company. This research deals with the analysis of the configuration of sets of Consumer Units of an electric energy distribution company. The analysis starts from the collection of historical data of occurrences that caused interruptions of electric energy for groups of consumers, identifying the average interruption times and the frequency with which they occurred throughout the analyzed period. The objective is to identify possible adjustments in the configuration of the sets of consumers, and for this, the methodology seeks to propose adjustments in the sets following restrictions and analysis of criteria imposed by ANEEL. Through the geographic visualization of the scope of the sets, two main criteria are analyzed before any adjustment between them, they are: contiguity between areas and number of consumer units per sets. For these criteria, matrices capable of informing the possibility of joining the sets to each other will be created. At the end of the application of the methodology, the results obtained for the collective indicators through the regrouping of sets are analyzed and a new configuration proposal is presented through two case studies, which allow the obtaining of scenarios that present a reduction in the values of the collective indicators through the union between two substations.